Pengaruh Deposit Mudharabah Terhadap Profit PT. Bank Sumut Syariah Tbk Kantor Cabang Binjai Tahun 2021 - Agus Kamizar; Muhammad Arfan Harahap (Lembaga Riset Ilmiah, 2022)
This study aims to determine the effect of the nominal amount of mudharabah deposits on the profits obtained by PT. Bank SUMUT Syariah Tbk Binjai Branch Office for the period 2019-2021. This type of research is quantitative research. The source of this research data is obtained from the financial statements of PT. Bank SUMUT Syariah Tbk Binjai Branch Office. Processing techniques and in this study using SPSS computer programs and Microsoft Office Excel. Data analysis techniques in this study used descriptive statistics, classical assumption test, hypothesis testing, and simple linear regression analysis. The results of the study show that there is a significant influence between mudharabah deposits on the profit of PT. Bank SUMUT Syariah Tbk Binjai Branch Office for the period 2019-2021 this is obtained from the results of the hypothesis test, namely the t-test which shows a significance value less than 0.05 (0.002 < 0.05) and a tcount > ttable (3.284 > 2.03224 ) then there is an effect of variable X on variable Y. Mudharabah deposits affect the profit of PT. Bank SUMUT Syariah Tbk Binjai Branch Office amounted to 21.8%, while the remaining 69.7% was influenced by other variables such as financing distribution, total bank capital, service income, fee-based income, and so on. There is a positive or in line relationship between Mudharabah Deposits (X) and Profit (Y), the higher the nominal amount of mudharabah deposits, the profit of PT. Bank SUMUT Syariah Tbk Binjai Branch Office will also be higher. Vice versa, if the nominal amount of mudharabah deposits has decreased, the profit of PT. Bank SUMUT Syariah Tbk Binjai Branch Office will also experience a decline.